Improving secondary prevention in coronary bypass patients: closing the audit loop. Issue 4 (16th March 2005) - Martin, T N; Irving, R J; Sutherland, M; Sutherland, K; Bloomfield, P
Abstract : Objectives: To complete the audit loop assessing secondary preventative care of patients who had had coronary artery bypass graft (CABG) surgery. Design: Two separate surveys of 1000 patients who had had CABG at the regional centre between 1988 and 1997, selected in 1998 and 2001. A single page questionnaire was sent to the patient's general practitioner. Interventions: A list was sent to each general practice in Lothian, Scotland, of their patients on the CABG database and the results of the original survey. Lothian Health organised a project to contact and recall patients with cardiac disease in each practice. Sixty five (of 128) practices participated. Main outcome measures: Blood pressure, smoking status, serum cholesterol concentrations, and prescription of lipid lowering drugs and aspirin. Results: 918 questionnaires (92%) in the second survey were returned describing 875 patients: 151 (17%) patients smoked and 752 patients (86%) took aspirin. Mean (SD) systolic blood pressure was lower in the second survey (142.5 (19.2) mm Hg in the first survey v 139.4 (19.1) mm Hg, p < 0.005). In our first survey 34% of patients had cholesterol concentrations less than target (5.2 mmol/l). This increased from 12% of patients operated on in 1988 to 50% of patients operated on in 1997 (Spearman rank correlation 0.77, p < 0.01). In the second survey this proportion had risen to 65% and the correlation with year of operation was abolished. Conclusions: By closing the audit loop, substantial improvements were shown in the management of risk factors in patients who have had coronary artery surgery in Lothian.